Description of Learning Motivation in Mathematics Learning for Class V Students of Imam Syafi'i Private Madrasah Ibtidaiyah, Gorontalo Regency - Suparsa, I Gede Aldi; Otoluwa, Moon Hidayati; Nurhayati, Lia (Sahabat Publikasi, 2024)
This research aims to describe learning motivation in mathematics learning for class v students at Madrasah Ibtidaiyah Swasta Imam Syafi'I, Gorontalo Regency. This research uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results showed students were diligent in doing assignments even though they experienced difficulties. They try to do assignments independently and ask other people; students always have the desire to try to answer the practice questions in the student's book without any criticism from any party, but not all students do it. Assignments on time, get low grades, don't give up, and will always try to improve by being more active in participating in learning.